The Role of Digital Learning Tools in Improving Students' English Skills: A Systematic Literature Review - Mira Tania (CV. ULIL ALBAB CORP, 2025)
The integration of digital learning tools has revolutionized English language education by increasing accessibility, effectiveness, and student engagement in the learning process. This study systematically reviews the role of digital tools in improving English language skills, focusing on their benefits, challenges, and practical implications. Findings indicate that digital tools significantly improve students’ reading, writing, speaking, and listening skills, supported by innovations such as mobile learning, augmented reality (AR), virtual reality (VR), and gamification. These tools not only personalize the learning experience but also encourage critical thinking and collaboration among students. Despite these benefits, challenges remain, including limited access to technology, inadequate infrastructure, and gaps in digital literacy among educators and students. Effective integration of digital tools into the curriculum requires ongoing professional development for teachers, development of engaging content, and equitable access to technology resources. Collaboration between educators, policymakers, and technology developers is essential to address these challenges. This study emphasizes the transformative potential of digital tools in English language education and calls for further studies to explore innovative applications of emerging technologies such as artificial intelligence and big data. By addressing existing barriers, digital tools can be optimized to create inclusive and dynamic learning environments that prepare students for the demands of a globalized digital future.